Talagrand’s Inequality in Hereditary Settings - Dubhashi, Devdatt P. (BRICS Report Series, 1998)
We develop a nicely packaged form of Talagrand's inequality that can be applied to prove concentration of measure for functions defined by hereditary properties. We illustrate the framework with several applications from combinatorics and algorithms. We also give an extension of the inequality valid in spaces satisfying a certain negative dependence property and give some applications.